2021
DOI: 10.1186/s13075-021-02555-2
|View full text |Cite|
|
Sign up to set email alerts
|

Nintedanib downregulates the transition of cultured systemic sclerosis fibrocytes into myofibroblasts and their pro-fibrotic activity

Abstract: Background Circulating fibrocytes are an important source of fibroblasts and myofibroblasts, which are involved in fibrotic processes, including systemic sclerosis (SSc). The study aimed to investigate the effect of nintedanib (a tyrosine kinase inhibitor) in inhibiting the in vitro transition of circulating SSc fibrocytes into myofibroblasts and their pro-fibrotic activity. Methods Circulating fibrocytes were obtained from 18 SSc p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Thus there exists not only the quantity difference, but also the activity difference possibly in S100A4 inside and outside cells. Patients with systemic sclerosis were found to have over‐expression S100A4 protein in their skin, resulting from the effect of fibroblasts 34 . And in the model of mice with systemic sclerosis, transforming growth factor (TGF)‐β was shown to be one of S100A4 activators via Smad3‐dependent pathway 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus there exists not only the quantity difference, but also the activity difference possibly in S100A4 inside and outside cells. Patients with systemic sclerosis were found to have over‐expression S100A4 protein in their skin, resulting from the effect of fibroblasts 34 . And in the model of mice with systemic sclerosis, transforming growth factor (TGF)‐β was shown to be one of S100A4 activators via Smad3‐dependent pathway 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with systemic sclerosis were found to have overexpression S100A4 protein in their skin, resulting from the effect of fibroblasts. 34 And in the model of mice with systemic sclerosis, transforming growth factor (TGF)-β was shown to be one of S100A4 activators via Smad3-dependent pathway. 14 In terms of patients with psoriasis, their expression of S100A4 in various types of dermis cells was up-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Nintedanib may also exert its anti-fibrotic efficacy by restraining the migration and differentiation of fibroblasts and fibrocytes. Interestingly, in vitro data have shown that nintedanib downregulates the transition of fibrocytes towards myofibroblasts, and thus the pro-fibrotic effect of the latter is reduced [ 197 , 198 ]. Nintedanib has received FDA approval for the treatment of IPF.…”
Section: Emerging Therapies With Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…In murine models of lung fibrosis, nintedanib inhibited macrophage and fibroblast activation and prevented fibrocyte migration 19–21 . In addition, nintedanib reduced the transition of fibrocytes to myofibroblasts and its pro‐fibrotic activity 22 . Nintedanib has been found to protect chondrocytes against tumor necrosis factor alpha‐induced degradation of the extracellular matrix against osteoarthritis 23 .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In addition, nintedanib reduced the transition of fibrocytes to myofibroblasts and its pro-fibrotic activity. 22 Nintedanib has been found to protect chondrocytes against tumor necrosis factor alpha-induced degradation of the extracellular matrix against osteoarthritis. 23 Synovial inflammation and fibrosis are also important pathological manifestations of OA, does nintedanib reduce OA by inhibiting synovial inflammation and fibrosis?…”
Section: Introductionmentioning
confidence: 99%